2017
DOI: 10.1002/anzf.1198
|View full text |Cite
|
Sign up to set email alerts
|

To Make Room or Not to Make Room: Clients’ Narratives About Exclusion and Inclusion of Spirituality in Family Therapy Practice

Abstract: This empirical article presents four narratives from an ongoing qualitative PhD project about spirituality and family therapeutic practice. Using case studies and narrative vignettes, the article presents client perspectives on being able to discuss their spirituality in therapy, and the repercussions when therapists exclude it. The article refers to current research and provides some reflections on how we can understand spirituality in the context of family therapeutic practice; therapists for holistic, cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Spirituality can be understood as a fundamental dimension of life and is expressed when interacting with others (Rykkje 2016). Spirituality can be expressed in various ways, some within a religious tradition and many within a secular context (Holmberg et al 2017). However, understanding the concept of spirituality can be a challenge because spirituality is understood to be private, and the connection spirituality has to religion may, for some, fit poorly in a secularized country like Norway (Kleiven et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality can be understood as a fundamental dimension of life and is expressed when interacting with others (Rykkje 2016). Spirituality can be expressed in various ways, some within a religious tradition and many within a secular context (Holmberg et al 2017). However, understanding the concept of spirituality can be a challenge because spirituality is understood to be private, and the connection spirituality has to religion may, for some, fit poorly in a secularized country like Norway (Kleiven et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Although multiculturalism has become an acknowledged key value in psychology, practitioners, instructors, and researchers seem to be a bit hesitant, particularly in regard to religious diversity (Plante, 2014). This also seems to occur in Norway, where both patients and practitioners report a lack of confidence in appropriately addressing existential and spiritual questions in psychotherapy (Holmberg et al, 2017;Ulland & DeMarinis, 2014). In a nationwide survey, Reme et al (2009) showed that students' expectations of learning about religion were far from being met in university teaching.…”
Section: Religiosity Gap and University Trainingmentioning
confidence: 99%
“…This trend has been slightly slower in Europe, but it has become noticeable. Recent studies conducted in Norway and Germany (Holmberg et al, 2017;Utsch et al, 2014) demonstrate the importance of integrating the spiritual dimension into therapy and counselling for patients, and the necessity for more study is regularly emphasised.…”
Section: Introductionmentioning
confidence: 99%
“…What would help to expand the interest and curiosity in clients’ spiritual perspectives in the family therapy field? This article presents a middle range theory2 called ‘the map of spiritual literacy’, based on a constructivist grounded theory study in systemic family therapy practice (Holmberg, Jensen & Ulland, 2017; Holmberg, 2018). The overarching aim of this study was to explore what spirituality means for family therapy practice in Norway, both from the therapist’s and client’s perspectives.…”
Section: Introductionmentioning
confidence: 99%
“… Australian & New Zealand Journal of Family Therapy , 2017, volume 38, special issue: ‘Family therapy and spirituality’. …”
mentioning
confidence: 99%